An antibody targeting type III secretion system induces broad protection against Salmonella and Shigella infections. - Raphaël Sierocki; Bakhos Jneid; Maria Lucia Orsini Delgado; Marc Plaisance; Bernard Maillère; Hervé Nozach; Stéphanie Simon (PLoS Neglected Tropical Diseases, 2021)
Salmonella and Shigella bacteria are food- and waterborne pathogens that are responsible for enteric infections in humans and are still the major cause of morbidity and mortality in the emerging countries. The existence of multiple Salmonella and Shigella serotypes as well as the emergence of strains resistant to antibiotics requires the development of broadly protective therapies. Recently, the needle tip proteins of the type III secretion system of these bacteria were successfully utilized (SipD for Salmonella and IpaD for Shigella) as vaccine immunogens to provide good prophylactic cross-protection in murine models of infections. From these experiments, we have isolated a cross-protective monoclonal antibody directed against a conserved region of both proteins. Its conformational epitope determined by Deep Mutational Scanning is conserved among needle tip proteins of all pathogenic Shigella species and Salmonella serovars, and are well recognized by this antibody. Our study provides the first in vivo experimental evidence of the importance of this common region in the mechanism of virulence of Salmonella and Shigella and opens the way to the development of cross-protective therapeutic agents.